Integrating straw yield and quality into multi-dimensional improvement of lentil (Lens culinaris) - Alkhtib, A.; Wamatu, Jane; Ejeta, Taye Tolemariam; Rischkowsky, Barbara A. (Wiley, 2017)
Lentil straw is an important source of fodder for livestock in Africa, South Asia and the Middle East. However, improvement programmes of lentil do not pay attention to straw traits, neither are straw traits considered in release criteria ofnew varieties. This study aimed to determine whether straw traits can be integrated into multi-trait improvement of lentil.